Gaza Rapid Damage and Needs Assessment, June 2021 - World Bank (World Bank, Washington, DC, 2021)
On May 20, 2021, after 11 days of the worst conflict since 2014, Israel and militants in Gaza agreed to a cessation of hostilities. Casualties were recorded on both sides, including more than 260 dead in Gaza according to the Palestinian Authority (PA) and the Office of the UN High Commissioner for Human Rights (OHCHR), along with considerable destruction of residential and commercial buildings. While in Israel, 9 Israelis and 3 foreign workers were killed according to the Israeli Ministry of Foreign Affairs. In Gaza, the conflict damaged various core physical and digital infrastructure assets, particularly buildings, hospitals and health centers, water and sanitation facilities, and transport, energy and communications networks. Exacerbated by previous trauma, this renewed round of violence having a particularly serious impact on children’s mental health as they are more susceptible to the effects of high levels of stress. Beyond the human tragedy and the subsequent immediate humanitarian relief that was channeled to Gaza, the economic impact of these 11 days of conflict has severely weakened an economy already reduced to a fraction of its potential. Gaza is one of the most densely populated areas in the world, with around 2.1 million individuals living in a total area of 365 square kilometers. For nearly 15 years, the movement of people and goods into and out of Gaza has been under restrictions imposed by the Government of Israel (GoI) due to security concerns. This isolation, in addition to multiple episodes of conflict and a damaging internal political divide, has created a severe humanitarian situation in Gaza that was exacerbated by the recent hostilities.